Reform in Healthcare Professions - Kamarulzaman, Adeeba binti; Mohd Dom, Tuti Ningseh; Saad, Zahrah; Musa, Muhamad Yusri (International Journal of Human and Health Sciences (IJHHS), 2023)
Healthcare professionals has been at the main frontline in the recent COVID-19 pandemic, battling through enormous difficulties including getting infected, burn-out, mental health issues, poor resource management and we lost a significant number of colleagues worldwide. Various challenges faced by health fraternity has led to calls for reform and significant steps taken by stakeholders including the Ministry of Health, Malaysia to improve working condition of healthcare workers (HCW) with formation of multiple committees, advisory board and most importantly the Health White Paper to ensure the word class standard of our health services remains relevant, sustainable and outstanding quality. Healthcare professionals such as doctors, dentists, nurses, paramedics and allied health professionals need to keep up with the changes and foresee upcoming challenges to ensure the integrity and quality of practices for each professions is kept at highest quality. International Journal of Human and Health Sciences Supplementary Issue: 2023 Page: S12